2012
DOI: 10.1371/journal.pone.0029086
|View full text |Cite
|
Sign up to set email alerts
|

GABA Expression and Regulation by Sensory Experience in the Developing Visual System

Abstract: The developing retinotectal system of the Xenopus laevis tadpole is a model of choice for studying visual experience-dependent circuit maturation in the intact animal. The neurotransmitter gamma-aminobutyric acid (GABA) has been shown to play a critical role in the formation of sensory circuits in this preparation, however a comprehensive neuroanatomical study of GABAergic cell distribution in the developing tadpole has not been conducted. We report a detailed description of the spatial expression of GABA immu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
28
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 121 publications
(174 reference statements)
2
28
0
Order By: Relevance
“…These studies were conducted by randomly sampling tectal neurons without knowledge of neurotransmitter phenotype, and therefore likely reflect changes in the majority excitatory neuron population. Little is known about inhibitory neurons in the developing tectum, except that GABA is hyperpolarizing in the tadpole stages studied here (Akerman and Cline, 2006; Tao and Poo, 2005) and visual experience increases GABA levels (Miraucourt et al, 2012), consistent with other reports (Hendry and Jones, 1988; Kreczko et al, 2009; Morales et al, 2002; Sarro et al, 2008). In addition, electrophysiological recordings indicate that tectal neurons do not yet display characteristic features of mature inhibitory neurons, such as fast spiking, at these developmental stages (Ciarleglio et al, 2015).…”
Section: Introductionsupporting
confidence: 90%
See 2 more Smart Citations
“…These studies were conducted by randomly sampling tectal neurons without knowledge of neurotransmitter phenotype, and therefore likely reflect changes in the majority excitatory neuron population. Little is known about inhibitory neurons in the developing tectum, except that GABA is hyperpolarizing in the tadpole stages studied here (Akerman and Cline, 2006; Tao and Poo, 2005) and visual experience increases GABA levels (Miraucourt et al, 2012), consistent with other reports (Hendry and Jones, 1988; Kreczko et al, 2009; Morales et al, 2002; Sarro et al, 2008). In addition, electrophysiological recordings indicate that tectal neurons do not yet display characteristic features of mature inhibitory neurons, such as fast spiking, at these developmental stages (Ciarleglio et al, 2015).…”
Section: Introductionsupporting
confidence: 90%
“…Inhibitory and excitatory neurons in the optic tectum are generated in a common proliferative zone and integrate into the optic tectal circuit at the same time (Akerman and Cline, 2006; Muldal et al, 2014). About 30% of optic tectal neurons are GABA-immunoreactive (Antal, 1991; Miraucourt et al, 2012), comparable to other brain regions and species (Caputi et al, 2013). Prior work has shown that visual experience promotes the structural and functional development of tectal neurons and the connectivity required for visual information processing (Ruthazer and Aizenman, 2010).…”
Section: Introductionmentioning
confidence: 69%
See 1 more Smart Citation
“…We defined stage 46 based on the NF criteria of having two to 2.5 turns of the intestine, slight rounding of the operculum edges, and the presence of the cement gland as a dominant anterior feature in the head (Nieuwkoop and Faber, 1956). Stage 47 encompasses considerable morphological and behavioral changes (Gilbert and Frieden, 1981;Karpinka et al, 2015;McKeown et al, 2013;Miraucourt et al, 2012;Nieuwkoop and Faber, 1956;Sharma and Cline, 2010;Shen et al, 2011), so we further divided stage 47 into early and late substages (Fig. 1B).…”
Section: Nutrient Availability Affects Growth and Developmentmentioning
confidence: 99%
“…By developmental stage 49 (ϳ16 dpf), the tectal neuron somata have organized into six compact somatic layers and have begun to display a range of different morphologies (Lazar 1973). Furthermore, a detailed immunohistochemical study indicates that even before developmental stage 49, the neurons across the tectum can be categorized as expressing either GABA or CaMKII and that the spatial pattern of GABA-expressing neurons has redistributed from clustered to being more evenly dispersed throughout the somatic layers (Miraucourt et al 2012). Although these morphological and immunohistochemical studies indicate that, even at relatively early developmental stages, tectal neurons are differentiating and reorganizing, the electrophysiology of the neurons beyond the deepest, most periventricular somatic layer, henceforth referred to as the "deep-layer" neurons, has not been described.…”
mentioning
confidence: 99%